Implementasi Pendidikan Karakter Siswa Melalui Program Boarding School Di Madrasah Tsanawiyah Darun Najah Payabenua - Dewi, Ratna (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Character education is a process in which a nation prepares its young generation to lead life and to fulfill life goals effectively. Related to this problem, it needs to be researched, which in this research is about: the implementation of student character education through the Islamic boarding school program at Madrasah Tsanawiyah Darun-Najah Payabenua. From this research, several conclusions regarding character education at Madrasah Tsanawiyah Darun Najah were produced: the implementation of the character education program includes: commemorating holidays, carrying out national day ceremonies, applying discipline values ​​by entering school on time. Implementing prayer activities before studying by reading the Koran, carrying out congregational prayers, and carrying out school cleanliness at Madasah Tsanawiyah Payabenua and others. Meanwhile, the obstacles in developing character education are: there are obstacles to education in general, there are obstacles to embedding character education in subjects, there are obstacles to developing devotion to worship, and there are obstacles to developing character education through habituation Pendidikan karakter merupakan suatu proses di mana suatu bangsa mempersiapkan generasi mudanya untuk menjalankan kehidupan dan untuk memenuhi tujuan hidup secara efektif. Dari penelitian ini dihasilkan beberapa kesimpulan tentang pendidikan karakter di Madrasah Tsanawiyah Darun Najah adalah: pada implementasi program pendidikan karater meliputi: memperingati Hari Besar, melaksanakan upacara hari nasional, menerapkan nilai disiplin dengan cara masuk sekolah tepat waktu. Menerapkan kegiatan berdo’a sebelum belajar dengan membaca Al-Qur’an, melaksanakan sholat berjama’ah, dan melaksanakan kebersihan sekolah di Madasah Tsanawiyah Payabenua dan lain-lainnya. Sedangkan kendala dalam mengembangkan pendidikan karakter yaitu: adanya kendala pendidikan secara umum, adanya kendala penanaman pendidikan karakter dalam mata pelajaran, adanya kendala pengembangan ketaatan beribadah, dan adanya kendala dalam pengembangan pendidikan karakter melalui pembiasaan